A Comparative Study of the Ability of the Cyperus Rotundus to Accumulate Heavy Metal in Southern of Iraq - Hamza, Shatha M. (American Journal of Botany and Bioengineering, 2025)
This experiment was conducted to evaluate concentration level of heavy metal pollutants ability of Cyperus rotundus to eliminate heavy metal from soli in different areas with in the southern region of Iraq, so, the study was conducted in three zones, zone 1 Grmma, zone 2 Shuiba, zone 3 Hartha. The study concluded that three areas were most polluted with lead, the highest concentration was in the Shuiba zone was noted in soil 7. 48±0. 21, and 6. 91±0. 81 in roots and4. 49±0. 33 in shoot. The lowest concentration of lead was found in Grmma zone1 in soil, roots and shoot. also concluded from this study the lowest concentration evaluate in of heavy metal is cadmium element was found with highest concentration in zone2 Shuiba 5. 64±0. 03, 4. 88±0. 08, 3. 99±0. 03 in soil. Roots and shoot respectively but the lowest concentration of heavy metal fined in soil and tissue of Cyperus rotundus in Grmma zone 1. The study also concluded that the Cyprus rotundas plant is efficient in removing pollutants from the soil and potential of this plant as phytodirector of pollution of soils in any areas. The TF, BAC and BCF were evaluate amount of heavy metals pollution in three zones were studied showed the three zones are pollute but by in different concentration.